Stereoselective Retentive Domino Transmetalations of Secondary Alkyllithium Compounds to Functionalized Secondary Alkylcopper Reagents. Issue 37 (14th August 2015) - Moriya, Kohei; Simon, Meike; Mose, Rasmus; Karaghiosoff, Konstantin; Knochel, Paul
Abstract Functionalized secondary alkyllithium reagents obtained by I/Li exchange from the corresponding secondary alkyl iodides undergo two successive transmetalations with Me3SiCH2ZnBr⋅LiBr and CuBr⋅2 LiCl⋅Me2S to provide functionalized secondary alkylcopper compounds with high retention of configuration. These alkylcopper derivatives react further with electrophiles such as alkynyl esters, acid chlorides, allylic chlorides, ketals, ethylene oxide, and 3‐iodocyclopentanone with high retention of configuration. A related sequence of transmetalations with MeMgI and LaCl3⋅2 LiCl allows a retentive addition of secondary alkyllithium reagents to acetone. The influence of the solvent on the configurational stability of secondary alkylzinc reagents is described.